Out of the shadows : the editor as a defining characteristic of journalism - Duffy, Andrew (2019)
The editor has often been hidden in scholarship under the catch-all term of ‘journalist’. Yet the roles of editor and reporter, while overlapping, are distinct. That distinction is essential to make because the editorial function is one of the defining characteristics of news journalism that separates it from ‘interloper media’ such as blogs, public relations (PR), government missives and citizen journalism. Editors are a marker of quality control which legitimises news journalism. This article scrutinises the editor as one who negotiates among four groups with distinct values: the audience, the organisation, journalism as practice, and society. Editor-centric analysis examines how individuals in editorial systems negotiate diverse elements of a fragmented phenomenon which is routinely unified under the banner of ‘journalism’. Clearer assessment of the editor thus allows for richer assessment of what is – and what is not – journalism. It directs discourse rooted in experience and ideology to legitimate journalism as a cultural form, leading consideration of how editor-centric study can be applied empirically.